Increased phenotypic differentiation and reduced corticosteroid sensitivity of fibrocytes in severe asthma - Lo,C-Y; Michaeloudes,C; Bhavsar,PK; Huang,C-D; Wang,C-H; Kuo,H-P; Chung,KF (Journal of Allergy and Clinical Immunology, 2014)
BackgroundPatients with severe asthma are less responsive to corticosteroid therapy and show increased airway remodeling. The mesenchymal progenitors, fibrocytes, may be involved in the remodeling of asthmatic airways. We propose that fibrocytes in severe asthma are different from those in nonsevere asthma.ObjectivesTo examine the survival, myofibroblastic differentiation, and C-C chemokine receptor 7 (CCR7) expression in blood fibrocytes from patients with severe and nonsevere asthma and study the effect of corticosteroids on fibrocyte function.MethodsThe nonadherent non–T-cell fraction of blood mononuclear cells was isolated from healthy subjects and patients with nonsevere and severe asthma. Total and differentiating fibrocytes were identified by their expression of CD45, collagen I, and α-smooth muscle actin using flow cytometry. The expression of CCR7 and of the glucocorticoid receptor was measured by using flow cytometry.ResultsIncreased numbers of circulating fibrocytes, with greater myofibroblastic differentiation potential, were observed in patients with severe asthma. Dexamethasone induced apoptosis, leading to reduction in the number of cultured fibrocytes and total nonadherent non-T cells from healthy subjects and patients with nonsevere asthma but not from patients with severe asthma. Dexamethasone reduced CCR7 expression in fibrocytes from patients with nonsevere asthma but not from patients with severe asthma. Glucocorticoid receptor expression was attenuated in fibrocytes from patients with severe asthma.ConclusionsPatients with severe asthma have elevated numbers of circulating fibrocytes that show enhanced myofibroblastic differentiation and that are less responsive to the effects of corticosteroids.